African Entrepreneurship 2018
DOI: 10.1007/978-3-319-73700-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship and SMEs’ Productivity Challenges in Sub-Saharan Africa

Abstract: translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Through the focus group, responses from individual interviews were verified and the possible omission of important Igbo cultural elements assumed (see e.g. Igwe, Madichie and Newbery, 2018; Igwe, Newbery and Icha-Ituma, 2018; Igwe, Onjewu and Nwibo, 2018; Nwankwo et al , 2010). This method allows the researcher to focus on the subject’s individual experience, and so explain the subject’s reality (Morse, 2006; Onwuegbuzie and Leech, 2005; Rolfe, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the focus group, responses from individual interviews were verified and the possible omission of important Igbo cultural elements assumed (see e.g. Igwe, Madichie and Newbery, 2018; Igwe, Newbery and Icha-Ituma, 2018; Igwe, Onjewu and Nwibo, 2018; Nwankwo et al , 2010). This method allows the researcher to focus on the subject’s individual experience, and so explain the subject’s reality (Morse, 2006; Onwuegbuzie and Leech, 2005; Rolfe, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…These obstacles add to the usual challenges that entrepreneurs face such as the lack of skilled labour, lack of market information, the time it takes to obtain permits, etc. (Igwe, Onjewu and Nwibo, 2018). Indeed, however, some entrepreneurs prevail despite the barriers and challenges.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results suggested that distance to physical infrastructure was not interpreted as farmers' ability to access markets; the sales of farming produce relied on changes in the marketing agents' behaviours. Igwe et al (2018) significantly indicated the enhancement of market orientation leading to the adoption of an entrepreneurial approach and the production of agricultural products commercially by sub-Saharan small-scale farmers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most small and medium-sized enterprises (SMEs) in Africa are managed by foreign entrepreneurs (Lebanese, Syrians, Pakistanis, Greeks, Portuguese, Indians, and Chinese) (Tshikuku, 2001). Apart from the many constraints and challenges related to the entrepreneurial ecosystem in Africa (lack of government support, paucity of funding, infrastructure problems, absence of training or management and marketing skills, lack of legislation on contracts, property and corruption) (Igwe et al, 2018; Olawale and Garwe, 2010), some other factors are undoubtedly related to culture or even African entrepreneurial abilities (risk propensity, networking, optimism, endurance, perseverance, etc.) (Asongu and Odhiambo, 2019; Igué, 2010; Tshikuku, 2001).…”
Section: Introductionmentioning
confidence: 99%